Senior-oriented robotic devices and algorithms for personalised fall prediction and prevention - Ribeiro, Nuno Miguel Ferrete (2022)
Doctoral Thesis (Doctorate in Leaders for Technical Industries / Engineering Design and Advanced Manufacturing LTI/EDAM - MIT Portugal)